Gone with the rain: negative effects of rainfall on male reproductive success in a nest-building arachnid - Valle, Andres Rojas (2018)
In nest-building species, offspring survival and reproductive success of parental individuals are strongly influenced by nest location and quality. Thus, quantifying the influence of abiotic conditions on nest integrity is important to predict the effects that weather variability may have on offspring survival and parental reproductive success. Here we investigated how rainfall affects nest integrity and how nest integrity influences male attractiveness and nest tenure. Our study species was the harvestman Quindina limbata, in which males build cup-like mud nests on fallen logs and protect the eggs against predators and fungi infestation. Our dataset is based on 12 months of regular inspections of over 150 nests in a tropical rainforest from Costa Rica. We found that 43% of the nests were destroyed by rainfall. The drag force promoted by rainfall running on the log surface negatively affected nest integrity by decreasing the wall perimeter and the floor area. The intensity of fungi cover was not explained by nest position or by precipitation. No matter the body size of the owner males, nests with high integrity received more eggs than nests with low integrity. Curiously, nests with high values of fungi cover received more eggs. Finally, nest integrity and fungi cover did not affect nest tenure, but the probability of males abandoning their nests increased with time they did not receive eggs. Considering that intense rainfall occurs all year long in tropical forests, the best males can do to decrease the chances of nest destruction is to select protected places to build their nests. Protected sites may keep nest structure better preserved, improve offspring survival, attract more females, and ultimately increase male reproductive success